2015
DOI: 10.1016/j.neuroimage.2015.03.043
|View full text |Cite
|
Sign up to set email alerts
|

Multi-vendor reliability of arterial spin labeling perfusion MRI using a near-identical sequence: Implications for multi-center studies

Abstract: Introduction: A main obstacle that impedes standardized clinical and research applications of arterial spin labeling (ASL), is the substantial differences between the commercial implementations of ASL from major MRI vendors. In this study, we compare a single identical 2D gradient-echo EPI pseudo-continuous ASL (PCASL) sequence implemented on 3T scanners from three vendors (General Electric Healthcare, Philips Healthcare and Siemens Healthcare) within the same center and with the same subjects. Material and me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
63
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 74 publications
(66 citation statements)
references
References 31 publications
2
63
1
Order By: Relevance
“…Moreover, the inter scanner reliability was also good at rest (ICC = 0.69) and during motor activation (ICC = 0.61) [33]. Only one small study explored more three 3 Tesla MRI platforms – GE, Philip and Siemens [31]. The authors compared similar pCASL acquisition parameters within the same day in two parallel studies, one with eleven subjects, and a second with fourteen subjects (eleven subjects participated in both studies).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, the inter scanner reliability was also good at rest (ICC = 0.69) and during motor activation (ICC = 0.61) [33]. Only one small study explored more three 3 Tesla MRI platforms – GE, Philip and Siemens [31]. The authors compared similar pCASL acquisition parameters within the same day in two parallel studies, one with eleven subjects, and a second with fourteen subjects (eleven subjects participated in both studies).…”
Section: Discussionmentioning
confidence: 99%
“…However, the study did not examine reliability across the three platforms as one unique group, but rather as two parallel investigations. Moreover, most other ASL reliability studies investigated CBF stability within a few hours [20,25,30,31] or within several days [20,24,25,29]. Overall, these studies reported high reliability for scans completed within the same day, and a decrease in reliability after several days.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Since then, numerous other studies have been published, comparing different sequences on a single manufacturer (138), near identical sequences on different manufacturers (139), and combinations in between. The general results confirm the same level of reproducibility, within and between subject standard deviations as originally found in the QUASAR reproducibility study (137).…”
Section: Reproducibility Inter-individual Variability and Snrmentioning
confidence: 99%
“…However, it should be noted that this is partly technical because we excluded the non-zero values which would otherwise artificially elevate the correlation coefficient without accurately reflecting meaningful CBF comparisons. Repeatability is a known problem with all perfusion techniques including pCASL 45 , Repeatability of H 2 [ 15 O] PET CBF has been recorded at 8% in WM and a 10% in GM over a two day interval between measurements 46 . Such variations are unlikely to have accounted for correlation differences given that pCASL and Bookend image acquisition were performed minutes apart Variability can be mitigated to some extent for pCASL using post-processing techniques that eliminate spurious voxels caused by small amounts of head motion 27 .…”
Section: Discussionmentioning
confidence: 99%